THE EFFECT OF MAULI BANANA (Musa acuminata) STEM EXTRACT ON MACROPHAGE CELL NUMBER IN PULP INFLAMATION (In Vivo Study In Male Wistar Rat (Rattusnovergicus) Teeth) - Astuti, Nadia Dewi; Laillyza Apriasari, Maharani; Ichrom Nahzi, Muhammad Yanuar (Dentino, 2018)
Background: Reversible pulpitis is a mild to moderate inflammatory condition of the pulp which often given pulp capping therapy as their treatments. Commonly used or "gold standard" material for pulp capping therapy is calcium hydroxide, but this material has side effect as an active therapeutic or chemical agent that can cause necrosis due to high pH. Mauli banana stem extract contains tannin and saponin compounds which have immunomodulatory properties that play a role in the pulp inflammatory process by increasing the number of macrophage. Objective: To prove the effect of mauli (Musa acuminata) banana extract gel concentration 37,5% upon macrophage cell count in pulp inflammation at day 3 and compare it with calcium hydroxide (Ca(OHâ)). Methods and Materials: This research was a pure experimental study with post-test only control group design. This research used 3 treatment groups, which were a group of mauli banana group of mauli banana extract gel 37,5% as treatment group, a group of calcium hydroxide as positive control group and a group of Hydroxypropyl Methyl Cellulose (HPMC) gel as negative control. Research Result: One Way Anova test results obtained p value = 0.0001 which means that there was a significant difference. Data analysis continued with Post Hoc Least Significant Difference (LSD) test which showed that there was significant difference between mauli banana extract gel concentration 37,5% with calcium hydroxide group with p value = 0,001 and with HPMC gel group p value = 0, 0001 (p <0,05), and there was no significant difference between the calcium hydroxide group and HPMC gel with p= 0,054 (p> 0,05). Conclusion: Provision of mauli banana extract gel 37,5% concentration can increase the number of macrophage cells on pulp inflammation on the 3rd day.